URGENSI PENGATURAN JAMINAN KREDIT DALAM SEKTOR PEER TO PEER (P2P) LENDING DI INDONESIA - Shania, Amalia Vanny; Kharisma, Dona Budi (Jurnal Privat Law, 2023)
This articles aims to analyse and examine the importance of implementing credit guarantee on peer to peer (p2p) lending mechanism in Indonesia as a form of prevention of Non Perfroming Loan Risk and the ideal type of credit guarantee to be applied on peer to per (p2p) lending mechanism. This research is a normative legal research with a perspective character with a consepual approach. The type of data used is secondary data which includes primary dan secondary legal materials. Meanwhile, the thechnique of collecting data in examining these problems use a literature study technique which is then carried out by technical analysis using the deductive method. The results show that there is urgency for the application of credit guarantee on peer to peer (p2p) lending sector based on 3 important aspects, namely philosophical, juridical, and sociological foundations. The urgency is related to the risk of non performing loan or default by the borrower which must be borne by the the lender. Implementing fiduciary security into peer to peer (p2p) lending mechanism can be an ideal solution to provide protection and legal certainty for lenders while minimizing the potentional risk of non performing loan.